MUP504 : Principal instrument III / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2025)
This course focuses on instrumental / vocal instruction in accordance to the student’s respective major and level of study. Students will discover and apply playing techniques, solve performance Issues, differentiate and apply stylistic interpretation, and memorize technical studies to produce refinement in a variety of pieces. Students attend a one-hour lesson and one-hour masterclass each week.